Використання методу квазіфункції Гріна-Рвачова для побудови ітераційних методів розв’язування деяких нелінійних крайових задач - Чернишов, Б. С. (ХНУРЕ, 2024)
The paper considers the application of the Green-Rvachev quasi-functions method to the construction of the various methods of successive approximations for the numerical analysis of the first boundary value problem for the semilinear elliptic equation with the elliptic operator.
Keywords: метод квазіфункції Гріна-Рвачова; нелінійна крайова задача; напівлінійне еліптичне рівняння